2003
DOI: 10.1126/science.1090284
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of Herpes Simplex Virus from Cryo-Electron Tomography

Abstract: Materials and Methods Strains, cultivation and purification of virions. African green monkey kidney (Vero) cells (CCL-81; ATCC, Mannasas, VA) and human foreskin fibroblasts (HFT) (S1) cells were grown in alpha-minimum essential medium supplemented with 10% fetal calf serum (Invitrogen, Carlsbad, CA) and passaged as described in Desai et al. (S2). Virus stocks were prepared in Vero cells as described (S2). HFT cells were infected with KOS virus at an MOI of 10 PFU/cell. 48

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
439
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 521 publications
(483 citation statements)
references
References 24 publications
30
439
0
5
Order By: Relevance
“…Indeed, it is known that proteins, such as Fc gamma receptors, can be indirectly raft associated through their affinity for other raft-associated proteins (16). Importantly, since lipid raft formation and protein association with lipid rafts occur in the Golgi complex (14), such a putative glycoprotein and tegument protein concentrating function of lipid rafts may also be significant for efficient alphaherpesvirus budding and particle formation, as has been hypothesized recently (17,23,26). In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, it is known that proteins, such as Fc gamma receptors, can be indirectly raft associated through their affinity for other raft-associated proteins (16). Importantly, since lipid raft formation and protein association with lipid rafts occur in the Golgi complex (14), such a putative glycoprotein and tegument protein concentrating function of lipid rafts may also be significant for efficient alphaherpesvirus budding and particle formation, as has been hypothesized recently (17,23,26). In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 89%
“…In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37). Further, the viral glycoprotein distribution in the HSV virion envelope has been shown to be nonrandom, which has been hypothesized to be caused by association of viral glycoproteins with lipid rafts (17). In addition, we have found that, like for human immunodeficiency virus (15,27), cholesterol in the PRV envelope is required for infectivity, since depletion of cholesterol from PRV preparations by using 10 mM MCD completely abolished PRV's ability to successfully infect susceptible cells (data not shown).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 99%
“…Using the conservative 0.5 criterion, the resolution of the complex was estimated to be 3.0 nm. One alternative criterion, which infers the correlation between a perfect reference and a reconstruction from the full data set, as proposed in (Grunewald et al, 2003;Rosenthal and Henderson, 2003) gives a resolution of 2.6 nm. Another alternative, accepting the 1/2 bit criterion formulated in (van Heel and Schatz, 2005), gives an estimate of 2.7 nm.…”
Section: Reconstruction Of Poliovirus-receptor-liposome Complexmentioning
confidence: 99%
“…Initially, this approach was applied to determine the structures of macromolecular complexes in vitro (Beck et al, 2004;Cardone et al, 2007;Chang et al, 2007;Cheng et al, 2007;Deng et al, 2007;Grunewald et al, 2003;Harris et al, 2006;Nicastro et al, 2005;Nicastro et al, 2006;Nickell et al, 2007;Zhu et al, 2006). Perhaps more excitingly, the approach has begun to be used to study macromolecular complexes within the context of intact cells.…”
Section: Introductionmentioning
confidence: 99%
“…The virion structure is of interest not only in the context of virus assembly but also in light of the possibility that pleiomorphic variations may correlate with infectivity and/or pathogenicity. As a step toward addressing these questions, we have used cryoelectron tomography, a technique capable of rendering the 3D structures of individual macromolecular particles in their native states (19)(20)(21)(22)(23)(24)(25), to visualize influenza virions of the type A eggadapted X-31 strain (26).…”
mentioning
confidence: 99%